New Families with Hereditary Hemorrhagic Trait due to Deficiency of Fibrin Stabilizing Factor (F. XIII) - Egeberg, O (Thrombosis and Haemostasis, 1968)
Severe hemorrhagic disorder due to congenital factor XIII deficiency is described in two unrelated Norwegian girls.Plasma cephalin time was for both patients extraordinarily short during episodes of bleeding and hematomas. No such hyperactivity reaction was demonstrable in unaffected condition some months later.Estimations of blood factor XIII levels revealed a partial defect in the parents of both children, and also in some other family members, consistent with an autosomal incompletely recessive inheritance of the defect. Some of the presumptive heterozygotes had a history of light bleeding phenomenons; whether this was related to their partial lack of factor XIII is so far uncertain.